(untitled) (Journal of the College of Basic Education, 2022)
The aim of the thesis: To identify the effect of quick ability exercises on the accuracy and speed of implementing the quick attack and some of the physical and motor abilities of basketball players The researcher used the experimental method, and the research sample consisted of (16) players, who is from the second Karkh breeding team in basketball. An equivalence was conducted among the sample members, then a pre-test was applied to it to extract the variables for the research. Then the application of the training units was adopted for each group, then the post-test was conducted to obtain the results in the same way, and the data was treated specialistly using the statistical methods (SPSS statistical bag). according to traditional exercises. The researcher recommends the necessity of adopting rapid ability exercises in the training units as it is an important factor in improving the physical, motor and skill abilities of the second Karkh basketball players, and to benefit from this study by the basketball coaches of the Iraqi club teams .